2007
DOI: 10.1523/jneurosci.5062-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Pathology in Prion Disease Starts at the Synaptic Spine

Abstract: Spine loss represents a common hallmark of neurodegenerative diseases. However, little is known about the underlying mechanisms, especially the relationship between spine elimination and neuritic destruction. We imaged cortical dendrites throughout a neurodegenerative disease using scrapie in mice as a model. Two-photon in vivo imaging over 2 months revealed a linear decrease of spine density. Interestingly, only persistent spines (lifetime Ն8 d) disappeared, whereas the density of transient spines (lifetime Յ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 52 publications
(76 reference statements)
1
114
0
Order By: Relevance
“…TPrP-treated PK1 cells underwent neuritic retraction and loss ( Fig. 1 E and H) that have been described as early signs of neuronal damage in prion diseases (31,32) as well as apoptosis (Fig. 3A), a feature of prion pathology (11).…”
Section: Similar Morphological and Molecular Hallmarks Of Tprp-inducedmentioning
confidence: 76%
“…TPrP-treated PK1 cells underwent neuritic retraction and loss ( Fig. 1 E and H) that have been described as early signs of neuronal damage in prion diseases (31,32) as well as apoptosis (Fig. 3A), a feature of prion pathology (11).…”
Section: Similar Morphological and Molecular Hallmarks Of Tprp-inducedmentioning
confidence: 76%
“…In prion diseases, apart from neuronal loss, earliest and potentially most vital neuropathology changes occur at the level of synapses including synapse loss, morphological changes, and functional abnormality (Mallucci, 2009). Two‐photon imaging studies of living, prion‐infected animals found that retraction of dendritic spines occur early during disease progression (Fuhrmann et al ., 2007; Fang et al ., 2016). Changes in their morphology are now believed to underlie synaptic plasticity associated with learning and memory, as well as degenerative events that occur during aging and neurological diseases (Sala & Segal, 2014; Herms & Dorostkar, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…dendrites (Fuhrmann et al, 2007) or synapses (Jeffrey et al, 2000), rather than at the soma of neurons. Thus, neuronenriched primary cultures used in the current study will be an invaluable ex vivo model for analysing the mechanism of neurodegeneration caused by prion infection.…”
Section: Discussionmentioning
confidence: 99%